Universal screening for hyperglycemia in early pregnancy and the risk of adverse pregnancy outcomes - Shen, Lixia; Zhang, Shaofeng; Wen, Jiying; Liu, Jia; Lin, Xiaohong; Zhu, Caixia; Cai, Shiqin; Xie, Lepei; Wang, Zilian; Chen, Haitian (BMC pregnancy and childbirth, 2025)
This study aimed to evaluate the screening outcomes in women with hyperglycemia in early pregnancy (fasting plasma glucose [FPG] 5.1-6.9 mmol/L and/or HbA1c 39-46 mmol/mol before 20 weeks of gestation). This multicenter retrospective cohort study was conducted in China between 2016 and 2022. In our setting, all women without pregestational diabetes performed both FPG and HbA1c screening at the first prenatal visit. Logistic regression models adjusted for confounders were performed to assess the associations of hyperglycemia in early pregnancy with adverse pregnancy outcomes. Subgroup analyses were explored according to the subsequent diagnosis of gestational diabetes (GDM, with or without). Of the 42,999 women in the analysis, 2515 (5.8%) women had hyperglycemia in early pregnancy. Compared with women with normal FPG and HbA1c levels, women with FPG 5.1-6.9 mmol/L and/or HbA1c 39-46 mmol/mol had a 3-fold increased risk of GDM (aOR 3.85; 95% CI 3.52-4.20), and 1-fold higher risk of hypertensive disorders of pregnancy (1.42; 1.20-1.67), shoulder dystocia (1.30; 1.11-1.52), preterm birth (1.30; 1.11-1.52), large-for-gestational-age (1.26; 1.12-1.43), and macrosomia (1.43; 1.19-1.73). Women with hyperglycemia in early pregnancy complicated by GDM were associated with a 50%, 84%, 48% and 24% increase in the odds of developing hypertensive disorders of pregnancy (1.50; 1.21-1.84), preterm premature rupture of membranes (1.84; 1.09-3.10), preterm birth (1.48; 1.22-1.81) and large-for-gestational-age (1.24; 1.05-1.45), respectively, compared with those without hyperglycemia. Pregnant women with hyperglycemia in early pregnancy have an increased risk of adverse pregnancy outcomes, and women with these conditions complicated by GDM are at higher risk than those without. Further research is needed to explore whether the incidence of GDM can be reduced by early intervention and therefore prevent the relevant adverse pregnancy outcomes.